Trimming the Sails : the Comparative Political Economy of Expansionary Fiscal Consolidations. (Central European University Press, 2008)
Fiscal consolidation has significant short term costs which dampen economic growth. This widely shared consensus in literature on political economy makes fiscal adjustment highly unpopular. Benczes conducts a systematic analysis to find out whether it is possible to have fiscal consolidation and experience economic growth even in the short run. The book provides a clear, multidisciplinary and systematic analysis of the relatively new concept of the so-called expansionary fiscal consolidations. This concept suggests that fiscal adjustment can be in trade-off with economic growth if certain conditions are met. But why do only a few countries and only at certain times experience the expansionary effects, while others not at all? The necessary conditions and circumstances have been totally neglected in the literature, or analyzed only partially at best. Having evolved a theoretical framework, it is tested on a difficult case: Hungary, which has had the highest deficit in the European Union. The main question was whether Hungary has a chance to experience short term growth effects in times of adjustment.